DOES EXPOSURE TO MUSIC VIDEOS PREDICT ADOLESCENTS' SEXUAL ATTITUDES? - Johannes W. J. Beentjes; Ruben P. Konig (European Scientific Journal, ESJ, 2013)
This study investigates whether exposure to music videos predicts adolescents' sexual attitudes when controlled for relevant characteristics of individuals and their social environment. Sexual attitudes are related to their music video use (i.e. exposure to music videos, peer group talk about music videos, and perceived realism of these videos), personal factors and the sexual norms they perceive in their social environment (i.e. sexual norms of their parents and friends). A survey among Dutch adolescents (age 13-18; N = 384) showed that time spent watching music videos, peer group discussions about music videos, and perceived realism of music videos are all positively related to the traditional attitudes that men dominate sexual relationships, and that women are sex objects. This relationship cannot be explained away with individual characteristics (i.e. gender, age, education), and the sexual norms that adolescents perceive in their social environment. So we conclude that it is very well possible that music videos play a role in the formation and reinforcement of traditional sexual attitudes.